Acanthoic acid suppresses lipin1/2 via TLR4 and IRAK4 signalling pathways in EtOH- and lipopolysaccharide-induced hepatic lipogenesis. (17th January 2018) - Song, Jian; Han, Xin; Yao, You-Li; Li, Ya-Mei; Zhang, Jing; Shao, Dan-Yang; Hou, Li-Shuang; Fan, Ying; Song, Shun-Zong; Lian, Li-Hua; Nan, Ji-Xing; Wu, Yan-Ling
Abstract: Objectives: In alcoholic liver disease, alcohol and lipopolysaccharide (LPS) are major stimulation factors of hepatic lipogenesis. Our objective was to determine the protective mechanism of acanthoic acid (AA) in EtOH- and LPS-induced hepatic lipogenesis. Methods: HSC-T6 cells were treated with ethanol (200 mm ) plus LPS (1 μg/ml) for 1 h, followed by AA (10 or 20 μm ) for another 6 h. C57BL/6 mice were pretreated with of AA (20 and 40 mg/kg) or equal volume of saline and then exposed to three doses of ethanol (5 g/kg body weight) within 24 h. The mice were sacrificed at 6 h after the last ethanol dosing. Key findings: Acanthoic acid significantly decreased the expressions of α-SMA, collagen-I, SREBP-1, and lipin1/2 induced, also decreased fat droplets caused by EtOH/LPS. AA treatment decreased the protein expressions of TLR4, CD14, IRAK4, TRAF3, p-TAK1 and NF-κB increased by EtOH/LPS on HSC cells. Results in vivo were consistent with results in vitro . Conclusions: Our data demonstrated that AA might modulate hepatic fibrosis and lipid deposition in HSC-T6 cell stimulated with ethanol combined with LPS by decreasing lipin1/2 via TLR4 and IRAK4 signalling pathways, and AA might be considered as a potential therapeutic candidate for alcoholic liver disease.